The incidence of exposure to antibiotics in children less than 6 years of age: a survey in a Portuguese metropolitan Area - Machado, Humberto S. (2016)
Background: The contact with antibiotics at an early age may lead to a number of nefarious consequences. Nevertheless, the amount of literature available on the usage of antibiotics in children is scarce. Taking into account the increasing emergence of resistant bacterial strains, it is imperative to study and make society aware of the excessive exposure of children to antibiotics. The purpose of this study was to evaluate the incidence of antibiotic therapy in children under the age of six, in the metropolitan area of Oporto. Methods: Surveys (concerning children born in the metropolitan area of Oporto since 2010) were conducted in several nursery schools, and its answers (n=1031) were subsequently analysed. Our primary outcome was the incidence of exposure to antibiotics in children under 6 years of age in the metropolitan area of Oporto. Statistical significance was set as a p value inferior to 0.05. Results: We verified that 958 children (92.9%) were exposed to antibiotics before the age of six. Additionally, five associations were found between the considered variables: cessation of treatment and number of times the child has resorted to antibiotics in his/her lifetime (p<0,0001); cessation of treatment and average of intake per year (p=0,021, R=0,082); child with chronic disease and number of times of usage during his/her lifetime (p=0,02); eldest child’s age and cessation of treatment (p=0,018); eldest child’s age and number of times of usage during the child’s lifetime (p=0,014, R=0,096). Conclusion: Our study revealed that the exposure to antibiotics in children under six years of age is exceptionally high. Furthermore, the presence of chronic disease seems to be associated with a higher frequency of antibiotic intake. Couples with older children had better antibiotic therapy compliance, as well as higher frequency of antibiotic intake.